The impact of exercise-induced muscle damage on various cycling performance metrics: a systematic review and meta-analysis - Devantier-Thomas, B.; Deakin, G. B.; Crowther, F.; Schumann, M.; Doma, K. (The Journal of Strength and Conditioning Research, 2024)
This systematic review and meta-analysis examined the impact of exercise-induced muscle damage (EIMD) on cycling performance. The primary outcome measure was cycling performance, whereas secondary outcome measures included creatine kinase (CK), delayed-onset muscle soreness (DOMS), and muscular contractions. Data were extracted and quantified through forest plots to report on the standardized mean difference and p values. The meta-analysis showed no significant change in oxygen consumption at 24-48 hours (p > 0.05) after the muscle damage protocol, although ventilation and rating of perceived exertion significantly increased (p < 0.05) during submaximal cycling protocols. Peak power output during both sprint and incremental cycling performance was significantly reduced (p < 0.05), but time-trial and distance-trial performance showed no change (p > 0.05). Measures of CK and DOMS were significantly increased (p < 0.05), whereas muscular force was significantly reduced following the muscle-damaging protocols (p < 0.05), confirming that cycling performance was assessed during periods of EIMD. This systematic review showed that EIMD affected both maximal and submaximal cycling performance. Therefore, coaches should consider the effect of EIMD on cycling performance when implementing unaccustomed exercise into a cycling program. Careful consideration should be taken to ensure that additional training does not impair performance and endurance adaptation.